Catheter Ablation of Ventricular Tachycardia in Patients With Arrhythmogenic Right Ventricular Cardiomyopathy/Dysplasia: A Sequential Approach. Issue 5 (5th March 2019) - Mathew, Shibu; Saguner, Ardan M.; Schenker, Niklas; Kaiser, Lukas; Zhang, Pengpai; Yashuiro, Yoshiga; Lemes, Christine; Fink, Thomas; Maurer, Tilman; Santoro, Francesco; Wohlmuth, Peter; Reißmann, Bruno; et al.
Abstract : Background: It has been suggested that endocardial and epicardial ablation of ventricular tachycardia (VT) improves outcome in arrhythmogenic right ventricular cardiomyopathy/dysplasia. We investigated our sequential approach for VT ablation in patients with arrhythmogenic right ventricular cardiomyopathy/dysplasia in a single center. Methods and Results: We included 47 patients (44±16 years) with definite (81%) or borderline (19%) arrhythmogenic right ventricular cardiomyopathy/dysplasia between 1998 and 2016. Our ablation strategy was to target the endocardial substrate. Epicardial ablation was performed in case of acute ablation failure or lack of an endocardial substrate. Single and multiple procedural 1‐ and 5‐year outcome data for the first occurrence of the study end points (sustained VT/ventricular fibrillation, heart transplant, and death after the index procedure, and sustained VT/ventricular fibrillation for multiple procedures) are reported. Eighty‐one radiofrequency ablation procedures were performed (mean 1.7 per patient, range 1–4). Forty‐five (56%) ablation procedures were performed via an endocardial, 11 (13%) via an epicardial, and 25 (31%) via a combined endo‐ and epicardial approach. Complete acute success was achieved in 65 (80%) procedures, and partial success in 13 (16%). After a median follow‐up of 50.8 (interquartile range, [18.6; 99.2]) months after the index procedure, 17 (36%) patients were free from the primary end point. After multiple procedures, freedom from sustained VT/ventricular fibrillation was 63% (95% CI, 52–75) at 1 year, and 45% (95% CI, 34–61) at 5 years, with 36% of patients receiving only endocardial radiofrequency ablation. A trend (log rank P =0.058) towards an improved outcome using a combined endo‐/epicardial approach was observed after multiple procedures. Conclusion: Endocardial ablation can be effective in a considerable number of arrhythmogenic right ventricular cardiomyopathy/dysplasia patients with VT, potentially obviating the need for an epicardial approach.